Concerning the Determination of the Geometrical Parameters of the Optical Element of a Deep-Water Surveillance System - N.A, Gasratova; V.S., Zuev; M.M, Trukhin (International Journal of Engineering and Technology, 2018)
This paper is devoted to the question of determining the geometrical parameters of the most common types of the optical element of the deep-sea porthole. The considered element is to be used as part of a lighting system operable at a depth of 5000 meters. The calculation was made without taking into account the influence of temperature.Â Â